2010
DOI: 10.1164/rccm.200812-1807oc
|View full text |Cite
|
Sign up to set email alerts
|

Gene Profiling of Clinical Routine Biopsies and Prediction of Survival in Non–Small Cell Lung Cancer

Abstract: Integration of functional genomics from small bronchoscopic biopsies allows molecular tumor classification and prediction of survival in NSCLC and might become a powerful adjunct for the daily clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 42 publications
2
23
0
1
Order By: Relevance
“…These results seem to be consistent with a more aggressive phenotype for the EGFR-2 and wt/wt-1 high-risk groups, as suggested by their overall higher CIN70 metagene expression, higher number of copy number alterations/amplifications, and association with a poorly differentiated tumor phenotype. In addition, our results, combined with previous reports (26,48,49), show the potential of applying prognostic/predictive gene expression signatures to small biopsy specimens from patients with nonoperable disease, provided that enough tissue material could be sampled.…”
Section: Discussionsupporting
confidence: 70%
“…These results seem to be consistent with a more aggressive phenotype for the EGFR-2 and wt/wt-1 high-risk groups, as suggested by their overall higher CIN70 metagene expression, higher number of copy number alterations/amplifications, and association with a poorly differentiated tumor phenotype. In addition, our results, combined with previous reports (26,48,49), show the potential of applying prognostic/predictive gene expression signatures to small biopsy specimens from patients with nonoperable disease, provided that enough tissue material could be sampled.…”
Section: Discussionsupporting
confidence: 70%
“…Attempts to detect gene expression in bronchoscopic or fine needle aspiration biopsies have emerged lately and not yet been applied broadly. Encouragingly, several recent studies have suggested that the limited amount of bronchoscopic or fine needle aspiration biopsies would allow establishing gene profiling and molecular tumor classification and might become a powerful adjunct for the daily clinical practice [31, 32]. Recently, Suwinski et al [33] have successfully integrated multiple molecular signatures from bronchoscopic biopsies into predicting clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression profiles obtained from this set of microarray data are derived, however, from highly heterogeneous clinical biopsies consisting of both tumor and activated stromal cells. In a previous study, Baty and colleagues revealed that prediction of survival was independent of tumor cell content present in each NSCLC biopsy (22). This suggests a strong predictive contribution from the tumor microenvironment compartments in NSCLC.…”
Section: Introductionmentioning
confidence: 95%